Bilayer CZTS/Si absorber for obtaining highly efficient CZTS solar cell. (December 2021) - Rahman, M.S.; Islam, S.; Khandaker, A.; Hossain, T.; Rashid, M.J.
Highlights: CZTS solar cell with bilayer CZTS/Si absorber exhibits an efficiency of 18.30% Insertion of Si enhances the generation by ∼ 30% and eventually improves the VOC. PV parameters seem invariant to Si layer thickness but not to the CZTS layer. Doping concentrations of both CZTS and Si layers affect the PV parameters. An estimated electric field of 2.676 MV/m is found at CZTS/Si interface. Abstract: The good photovoltaic (PV) properties of Cu2 ZnSnS4 (CZTS) and silicon (Si) can be used combinedly as a potential route for enhancing the efficiency of CZTS solar cell. In this work, a bilayer CZTS/Si absorber structure is presented to replace the conventional single CZTS absorber layer based solar cell. The numerical tool SCAPS-1D is utilized first to validate the structure with the help of J-V characteristics, generation rate, quantum efficiency and band diagrams. A similar tool is used afterwards to optimize the proposed structure considering different parameters such as layer thickness, defect density, carrier concentration and operating temperature. The highest yielded efficiency of the bilayer structure is 18.30% (VOC  = 0.883 V, JSC  = 25.90 mA/cm 2 ). The thickness of both CZTS and Si layers are optimized and its effect on the performance parameters are discussed. The p-type doping concentrations of both layers are studied for the suitable range and optimized. Also, the electric field at the CZTS/Si interface is estimated. Next, the defect state density and operating temperature are varied to see the solar cell performances. The studied results provide a clear indication of the performance improvement of the CZTS solar cell using the bilayer CZTS/Si absorber structure.